Black-light continuum generation in a silica-core photonic crystal fiber - Sylvestre, Thibaut; Ragueh, A. R.; Lee, M. W.; Stiller, Birgit; Fanjoux, G.; Barviau, Benoit; Mussot, Arnaud; Kudlinski, Alexandre (Optics Letters, 2012)
We report the observation of a broadband continuum spanning from 350 to 470 nm in the black-light region of the electromagnetic spectrum as a result of picosecond pumping a solid-core silica photonic crystal fiber at 355 nm. This was achieved despite strong absorption and a large normal dispersion of silica glass in the UV. Further investigations reveal that the continuum generation results from the interplay of intermodally phase-matched fourwave mixing and cascaded Raman scattering. Wealso discuss the main limitations intermsof bandwidth and power due to temporal walk-off, fiber absorption, and the photo darkening effect, and we suggest simple solutions. © 2012 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29